The personalized antithrombotic management of atrial fibrillation with intermediate thromboembolic risk: a case report. Issue 5 (9th September 2020) - Hammer, Andreas; Schnaubelt, Sebastian; Niessner, Alexander; Sulzgruber, Patrick
Abstract: Background: So far there has been little evidence on the antithrombotic treatment of patients presenting with atrial fibrillation (AF) and a CHA2 DS2 -VASc score of 1 in men (2 in women). However, a recently published position paper suggests a personalized approach in weighing individual risk factors and considering additional patient characteristics and biomarkers for the decision for or against antithrombotic treatment in this intermediate-risk AF population. Case summary: A 63-year-old male patient with a CHA2 DS2 -VASc score of 1 due to hypertension presents with a first episode of paroxysmal AF. The European Society of Cardiology (ESC) guidelines on the management of AF do not recommend a general antithrombotic therapy in those patients. Therefore, the decision for or against the initiation of oral anticoagulation (OAC) in the presented case is based on recent treatment recommendations of the ESC, that aim to guide clinicals through the question whether to anticoagulate or not. Discussion: Oral anticoagulation in patients presenting with a CHA2 DS2 -VASc of 1 remains a challenging approach in clinical practice and physicians need to carefully balance the individual benefit of reducing thromboembolic risk with OAC against the potential harm due to an increase in bleeding risk in this patient population. The ESC provided an easily applicable approach for decision-making in patients with AF and a CHA2 DS2 -VASc score of 1 via consideration of additional risk factors, scoring tools, and established biomarkers. Of note, if an antithrombotic therapy is offered, non-vitamin K antagonist oral anticoagulants should be preferred over vitamin K antagonists based on the beneficial net clinical benefit.